Pengaruh Sari Kurma Terhadap Kenaikan Kadar Hemoglobin Ibu Hamil Dengan Anemia Di Puskesmas Aur Duri Kota Jambi Tahun 2024 - Dewi Junita; Susilawati (STIKes Budi Mulia Sriwijaya, 2024)
The need for iron in pregnant women increases so that an additional 700-800 mg is needed. Iron deficiency can cause disturbances or inhibition of fetal growth, both body cells and brain cells. Dates are one of the fruits that contain iron (fe) which is sufficient to meet the needs of iron, vitamin C, vitamin B complex and folic acid which can help form red blood cells. The aim of this study was to determine the effect of date palm juice on increasing hemoglobin levels in pregnant women with anemia at the Aur Duri Health Center in 2024. Pre-experimental research with the one Group Pretest Posttest design. The population in this study were all pregnant women who visited the Aur Duri Health Center in Jambi City. The sample in this study was taken by accidental sampling, amounting to 30 pregnant women with anemia. The statistical tests used were univariate with a frequency distribution and bivariate with the Wilcoxon test. The results showed that before being given palm juice, the average hemoglobin level in pregnant women was 9.23 (mild anemia), after being given palm juice, the average hemoglobin level in pregnant women was 12.35 (not anemic). The results of the Wilcoxon test are p-value = 0.000 <0.05, so Ho is rejected and Ha is accepted. This shows that there is an effect of date palm juice on increasing hemoglobin levels in pregnant women with anemia. The conclusion in this study is that date juice has an effect on increasing hemoglobin levels in pregnant women with anemia at the Aur Duri Health Center in 2024. Suggestions are expected for Health Centers to apply it in ANC services and provide knowledge to pregnant women about to increase hemoglobin levels in pregnant women, namely by non-pharmacological treatment by administering date palm juice.how.